2023
DOI: 10.1200/op.23.00191
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Relapse in Australian Patients With Clinical Stage 1 Testicular Cancer: Utility of the Australian and New Zealand Urogenital and Prostate Cancer Trials Group Surveillance Recommendations

Abstract: PURPOSE: International guidelines advocate for active surveillance as the preferred treatment strategy for patients with stage 1 testicular cancer after orchidectomy although a personalized discussion is required. MATERIALS AND METHODS: We conducted an analysis of individuals registered in iTestis, Australia's testicular cancer registry, to describe the patterns of relapse and outcomes of patients treated in Australia where the Australian and New Zealand Urogenital and Prostate Cancer Trials Group Surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The reason is simple—it is a very well-conducted study of 650 patients, multicenter and multidisciplinary, with long follow-up and a real-world flavor in its measurement of outcomes. 1 In short, it adds to the published literature in a meaningful way and emphasizes the following:active surveillance in the hands of ANZUP investigators is safe, with predominantly good-risk patterns of relapse;most relapses these days are detected by imaging or the combination of imaging and measurement of serologic markers;both seminoma and NSGCT can be managed via active surveillance with safety.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The reason is simple—it is a very well-conducted study of 650 patients, multicenter and multidisciplinary, with long follow-up and a real-world flavor in its measurement of outcomes. 1 In short, it adds to the published literature in a meaningful way and emphasizes the following:active surveillance in the hands of ANZUP investigators is safe, with predominantly good-risk patterns of relapse;most relapses these days are detected by imaging or the combination of imaging and measurement of serologic markers;both seminoma and NSGCT can be managed via active surveillance with safety.…”
mentioning
confidence: 98%
“…In the article that accompanies this editorial, Conduit et al 1 have reported the Australian & New Zealand Urogenital and Prostate Cancer Trials Group (ANZUP) experience of surveillance for stage I testis cancer, to our knowledge, perhaps one of the largest series to date. It seems appropriate to complete the circle of Commonwealth contribution in this domain as active surveillance for stage I testicular cancer largely arose from the United Kingdom and the antipodes more than 40 years ago.…”
mentioning
confidence: 99%
“…First introduced in the 1980s, active surveillance for clinical stage 1 testicular cancer after orchidectomy has been embraced ( 5 , 6 ), and is now preferred to adjuvant therapy in most consensus guidelines ( 7 - 9 ). Whilst highly efficacious at preventing relapse ( 10 - 12 ), adjuvant treatment with chemotherapy or radiotherapy is associated with potential short- and long-term toxicities that may have persisting impacts on quality of life for long-term survivors and pertinently, is unnecessary for the majority ( 1 ).…”
mentioning
confidence: 99%
“…Active surveillance delicately navigates the risk of over-investigation and over-treatment, with the risks of recurrent testicular cancer, using a protocolised approach encompassing physical examination, regular imaging, and serum tumour biomarkers evaluation ( 6 - 9 , 15 , 16 ). These recommendations have been designed to proactively detect recurrences in the unlikely event they occur.…”
mentioning
confidence: 99%
See 1 more Smart Citation